Manejo de irrigação da batata, pêra e maçã no Uruguai - Gallarreta, Claudio Cesar Garcia (2006)
The objective of this work was to evaluate the utilization of different values of maximum crop evapotranspiration as irrigation trigger on growth, yield and yield components of potato, pear and apple plants. Experiments were conducted during 2002/03 and 2003/04 growing season in commercial fields, in southern Uruguay. Potato irrigation experiments were conducted in three areas each year, in San José County. In 2002/03 growing season experiments were located: (i) Libertad, in an area irrigated with central pivot, and other with a big gun and (ii) Colônia Galland, an area irrigated with lateral system. In 2003/04 growing season the experiments were located: (i) Libertad, in an area irrigated with a big gun; (ii) Rincón del Pino, an area irrigated with big gun and, (iii) Colônia Galland, an area irrigated with lateral system. Irrigation experiments in pear and apple were conducted in commercial orchards during 2003/04 growing season. A completely randomized design was used with three replications. Potato plants were submitted to three irrigation treatments during the two years. Potato plants in an irrigation area with central pivot were submitted to two treatments (15 mm irrigation depth and no irrigation). Irrigations were applied when cumulative daily maximum crop evapotranspiration (ETma), estimated by the Penman-Monteith equation, reached the value of 35 mm. In the pear and apple irrigation experiments plants were submitted to three irrigated treatments: Irrigations were applied when ETma reached 30, 45 and 60 mm. Results demonstrated that there were differences in leaf area index and plant height of potato at 70 DAE, and 62 and 70 DAE, respectively in Libertad area (2002/03 growing season). Total potato yield presented maximum technical efficiency (43 ton ha-1) with the application of 143 mm of irrigation depth in Colônia Galland area in 2003/04 growing season, and in Libertad reached 39 ton.ha-1 and 47 ton.ha-1 in 2002/03 and 2003/04 growing season with the application of 98 and 144 mm, respectively. Irrigation management applying 25 mm of irrigation depth always when ETma reached values of 35 mm, resulted in highest yield. Maximum technical efficiency (48 ton ha-1) was verified with the application of 137 mm of irrigation depth. Potato yield in treatments without irrigation was 27.8 ton.ha-1, 42% of yield reduction compared with irrigated treatments. In the irrigation pear experiment no differences were observed for fruit growth, height plants, plant canopy and trunk cross area section among all irrigation management tested. The maximum technical efficiency for total yield (58,8 ton ha-1) was verified for irrigation depth of 8 mm when cumulative maximum crop evapotranspiration reached value of 35 mm as irrigation trigger. In the apple irrigation experiment no differences were observed for fruit growth, height plants, plant canopy and trunk cross area section among all irrigation managements tested. A máxima eficiência técnica (70 ton ha-1) para a produção total de frutos de maçã foi verificada com a aplicação de irrigação de 8 mm sempre que a evapotranspiração máxima acumulada da cultura atingia 45 mm de lâmina acumulada. The maximum technical efficiency for total yield (70 ton ha-1) was verified for irrigation depth of 8 mm when cumulative maximum crop evapotranspiration reached value of 45 mm as irrigation trigger.